2019
DOI: 10.1016/j.arth.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic Classification Criteria of ARCO on Femoral Head Osteonecrosis Part 2: Alcohol-Associated Osteonecrosis

Abstract: Objective: Although alcohol is a leading risk factor for osteonecrosis of the femoral head (ONFH) and its prevalence reportedly ranges from 20% to 45%, there are no unified classification criteria for this subpopulation. In 2015, Association Research Circulation Osseous (ARCO) decided to develop classification criteria for alcohol-associated ONFH (AA-ONFH). Methods: In June of 2017, ARCO formed a task force to conduct a Delphi survey. The task force invited twenty-eight experts in osteonecrosis/bone circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 44 publications
0
44
0
1
Order By: Relevance
“…Alcohol consumption is considered as a vital risk factor for non‐traumatic ONFH . A myriad of epidemiologic studies indicated that a substantial number of ONFH patients were due to alcohol overuse .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol consumption is considered as a vital risk factor for non‐traumatic ONFH . A myriad of epidemiologic studies indicated that a substantial number of ONFH patients were due to alcohol overuse .…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathogenesis of non‐traumatic ONFH has not been fully elucidated, several risk factors have been identified, including corticosteroids medication, alcohol consumption and several autoimmune diseases . Actually, alcoholism is one of the leading risk factors for ONFH worldwide, and epidemiologic studies indicated that 20%‐45% of ONFH patients were due to alcohol overuse …”
Section: Introductionmentioning
confidence: 99%
“…Of the 123 patients who were diagnosed with ONFH and underwent CT, 27 had pre-collapse ONFH with an ARCO stage of 1 or 2, 6 which satisfied the previously described ROI condition ( Table 1) Factors associated with ONFH included corticosteroid usage in 15 patients and alcohol abuse in 12 patients. 18,19 Several characteristics differed significantly between ONFH and control participants, particularly sex (p < .01). Therefore, propensity score matching was conducted to unify the baseline characteristics.…”
Section: Differences In Hu Values Between Patients With Pre-collapsmentioning
confidence: 99%
“…However, the outcomes were individually different; therefore, the factors that led to this difference were investigated. First, etiology was revealed as a predictor [18,19], but in the present study, it was unlikely significant and violated the proportional hazards assumption. Gender (P = 0.2599), age (P = 0.0730), BMI (P = 0.0015), HHS (P < 0.0001), and ARCO stage (P = 0.4853) were than analyzed as independent risk factors for progression.…”
Section: Discussionmentioning
confidence: 54%